Traditional Chinese Medicine in the Treatment of Chronic Kidney Diseases: Theories, Applications, and Mechanisms - Wang, Yunlai; Feng, Ye; Li, Manman; Yang, Mo; Shi, Gaoxiang; Xuan, Zihua; Yin, Dengke; Xu, Fan (Frontiers in Pharmacology, 2022)
Chronic kidney disease (CKD) is a common and progressive disease that has become a major public health problem on a global scale. Renal fibrosis is a common feature in the pathogenesis of CKD, which is mainly related to the excessive accumulation and deposition of extracellular matrix (ECM) caused by various inflammatory factors. There is no ideal treatment that has been established. In recent years, based on the traditional Chinese medicine (TCM) theory of CKD and its molecular mechanism, clinical evidence or experimental studies have confirmed that a variety of Chinese materia medica (CMM) and its effective components can delay the progress of CKD. TCM believes that the pathogenesis of CKD is the deficiency in root and excess in the branch, and the deficiency and excess are always accompanied by the disease. The strategies of TCM in treating CKD are mainly based on invigorating Qi and tonifying kidney, promoting blood circulation and removing stasis, eliminating heat and dampness, removing turbidity, and eliminating edema, and these effects are multi-targeted and multi-functional. This review attempts to summarize the theories and treatment strategies of TCM in the treatment of CKD, and presents the efficacy and mechanisms of several CMMs supported by clinical evidence or experimental studies. In addition, the relationship between the macroscopic of TCM and the microscopic of modern medicine and the problems faced in further research were also discussed.